Analisis Tingkat Pemborosan Lean Warehousing dengan Metode Value Stream Mapping dan FMEA di Warehouse Penyimpanan PT.XYZ - Sinaga, Boriski; Rochmoeljati, Rr. (Ekonomis: Journal of Economics and Business, 2025)
This study aims to determine the level of waste that occurs in the warehousing process at PT. XYZ through the implementation of lean warehousing. Data analysis in this study uses the lean warehousing method, namely Value Stream Mapping (VSM) to find critical waste in the warehousing process using the Waste Assessment Model (WAM) which then identifies the root causes of waste using a fishbone diagram and analyzes improvement recommendations using the FMEA method. Based on the results of the study, it is known that the levels of critical waste from the highest to the lowest, respectively, are waste waiting, waste unnecessary motion, waste over-processing, and waste defect. Based on the fishbone diagram analysis, there are 6 factors that cause the four critical wastes, namely human factors, method, material, environment, measurement, and machine. The proposed improvements that are the result of the analysis using FMEA are implementing the 5S concept in the warehouse, implementing a FIFO system for placing goods in the warehouse, increasing the number of workers, optimizing employee placement, and implementing a warehouse management system.